Review—Critical considerations of high quality graphene synthesized by plasma-enhanced chemical vapor deposition for electronic and energy storage devices - Mohd Abid, Mohd Asyadi Azam; Zulkapli, Nor Najihah; Dorah, Norasimah; Raja Seman, Raja Noor Amalina; Ani, Mohd Hanafi; Sirat, Mohd Shukri; Ismail, Edhuan; Fauzi, Fatin Bazilah; Mohamed, Mohd Ambri; Majlis, Burhanuddin Yeop (Electrochemical Society (ECS), 2017)
Graphene is a promising electrode material not only due to its intrinsic properties like good electrical conductivity, high mechanical strength and high chemical stability, but also because of its high theoretical surface area of 2630 m2 g−1. In this report, the effect of CVD parameters to the growth of high quality graphene on metal substrates by using plasma enhanced chemical vapor deposition (PECVD) was extensively studied. Interestingly, synthesizing high quality graphene by PECVD technique is not only depending on the CVD parameters, but also depending on the catalysts and its plasma sources. It was found that Ni and Cu are the most favored metal catalysts for PECVD graphene growth. With high solubility of carbon (> 0.1 at. %), Ni effectively promote the growth of multilayer graphene by PECVD. However, large-area synthesis has made relatively inexpensive Cu as one of the most attractive substrates for monolayer graphene growth. Further details on the potential use of different transition metal catalysts in synthesizing graphene and consequently the specific usage of graphene based devices are discussed in this report.